Liraglutide Treatment Reduces Endothelial Endoplasmic Reticulum Stress and Insulin Resistance in Patients With Diabetes Mellitus. Issue 18 (18th September 2018) - Bretón‐Romero, Rosa; Weisbrod, Robert M.; Feng, Bihua; Holbrook, Monika; Ko, Darae; Stathos, Mary M.; Zhang, Ji‐Yao; Fetterman, Jessica L.; Hamburg, Naomi M.
Abstract : Background: Prior studies have shown that nutrient excess induces endoplasmic reticulum (ER) stress in nonvascular tissues from patients with diabetes mellitus (DM). ER stress and the subsequent unfolded protein response may be protective, but sustained activation may drive vascular injury. Whether ER stress contributes to endothelial dysfunction in patients with DM remains unknown. Methods and Results: To characterize vascular ER stress, we isolated endothelial cells from 42 patients with DM and 37 subjects without DM. Endothelial cells from patients with DM displayed higher levels of ER stress markers compared with controls without DM. Both the early adaptive response, evidenced by higher phosphorylated protein kinase–like ER eukaryotic initiation factor‐2a kinase and inositol‐requiring ER‐to‐nucleus signaling protein 1 ( P =0.02, P =0.007, respectively), and the chronic ER stress response evidenced by higher C/EBPα‐homologous protein ( P =0.02), were activated in patients with DM. Higher inositol‐requiring ER‐to‐nucleus signaling protein 1 activation was associated with lower flow–mediated dilation, consistent with endothelial dysfunction ( r =0.53, P =0.02). Acute treatment with liraglutide, a glucagon‐like peptide 1 receptor agonist, reduced p‐inositol‐requiring ER‐to‐nucleus signaling protein 1 ( P =0.01), and the activation of its downstream target c‐jun N‐terminal kinase ( P =0.025) in endothelial cells from patients with DM. Furthermore, liraglutide restored insulin‐stimulated endothelial nitric oxide synthase activation in patients with DM ( P =0.019). Conclusions: In summary, our data suggest that ER stress contributes to vascular insulin resistance and endothelial dysfunction in patients with DM. Further, we have demonstrated that liraglutide ameliorates ER stress, decreases c‐jun N‐terminal kinase activation and restores insulin‐mediated endothelial nitric oxide synthase activation in endothelial cells from patients with DM.